2013
DOI: 10.1094/phyto-10-12-0272-r
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Ceratocystis smalleyi Infections Associated with Reduced Stem Water Transport in Bitternut Hickory

Abstract: Hundreds of cankers caused by Ceratocystis smalleyi are associated with hickory bark beetle-attacked bitternut hickory exhibiting rapid crown decline in the north-central and northeastern United States. Discolored sapwood colonized by the fungus commonly underlies the cankers. Field studies were conducted to test the hypothesis that C. smalleyi infections cause vascular system dysfunction in infected trees. Fifty C. smalleyi inoculations made at 1.8 to 3.8 m in height on stems of healthy bitternut hickory tree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 21 publications
0
31
0
Order By: Relevance
“…As previously reported by Araújo et al, (2014), C. fimbriata extensively colonize the pith parenchyma in the radial direction in the stem tissues of plants from susceptible mango cultivars, such as Espada and Haden; in contrast, in resistant cultivars, the fungal hyphae barely reach these cells. The formation of these defense structures, together with the tissue colonization itself and increasing structural damages, ultimately lead to an increase in sap flow resistance and may result in an altered plant hydration status (Nogués et al, 2002;Dong et al, 2012;Park et al, 2013). In due course, the alterations in water availability may lead to reductions in photosynthesis, transpiration rates, leaf longevity and integrity (Nogués et al, 2002) as observed for a series of other pathosystems that also involve the mango-C. fimbriata interaction .…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported by Araújo et al, (2014), C. fimbriata extensively colonize the pith parenchyma in the radial direction in the stem tissues of plants from susceptible mango cultivars, such as Espada and Haden; in contrast, in resistant cultivars, the fungal hyphae barely reach these cells. The formation of these defense structures, together with the tissue colonization itself and increasing structural damages, ultimately lead to an increase in sap flow resistance and may result in an altered plant hydration status (Nogués et al, 2002;Dong et al, 2012;Park et al, 2013). In due course, the alterations in water availability may lead to reductions in photosynthesis, transpiration rates, leaf longevity and integrity (Nogués et al, 2002) as observed for a series of other pathosystems that also involve the mango-C. fimbriata interaction .…”
Section: Discussionmentioning
confidence: 99%
“…Ceratocystis fimbriata are primarily xylem pathogens (Harrington 2000), thus vessel colonization and the development of internal tissue necrosis may provoke the disruption of sap flow, leading to the development of leaf water shortages and, consequently, wilt symptoms (Al-Sadi et al 2010;Park et al 2013). The impairment of the regular flow of water throw the soil-plant-atmosphere continuum generally leads to the initiation of adaptive responses, such as stomatal closure, in order to minimize the water loss by transpiration (Christmann et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Pierce's disease causes grapevines to enter into a state of unreturned decline; therefore, the plants no longer have the resources to support the production of secondary metabolites with antimicrobial activity (Wallis and Chen 2012). It is known that, in a state of decline, the physiology of the diseased plants cannot be returned to adequate levels, therefore causing them to enter into a survival mode (Park et al 2013;Wallis and Chen 2012). Thus, higher concentrations of phenolics could be found in tissues of non-infected plants than in the infected ones (Wallis and Chen 2012).…”
Section: Discussionmentioning
confidence: 99%